2017
DOI: 10.1017/s0266462317000265
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sample Size Estimation in Trials of Medical Devices: High-Risk Devices for Neurological Conditions as Example

Abstract: Our systematic review of trials on high-risk MDs confirms previous research, which has documented deficiencies regarding data availability and a lack of reporting on sample size calculation. More effort is needed to ensure both relevant sources, that is, original research protocols, to be publicly available and reporting requirements to be standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, it could be shown that there were also discrepancies between sample sizes in publications and protocols 14. Another study documented that only 31 out of 71 studies (protocol/publication) provided information on how the sample size was calculated (26 complete descriptions) 15…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could be shown that there were also discrepancies between sample sizes in publications and protocols 14. Another study documented that only 31 out of 71 studies (protocol/publication) provided information on how the sample size was calculated (26 complete descriptions) 15…”
Section: Discussionmentioning
confidence: 99%